Quantification of blue carbon pathways contributing to negative feedback on climate change following glacier retreat in West Antarctic fjords. (17th October 2021) - Zwerschke, Nadescha; Sands, Chester J.; Roman‐Gonzalez, Alejandro; Barnes, David K. A.; Guzzi, Alice; Jenkins, Stuart; Muñoz‐Ramírez, Carlos; Scourse, James
Abstract: Global warming is causing significant losses of marine ice around the polar regions. In Antarctica, the retreat of tidewater glaciers is opening up novel, low‐energy habitats (fjords) that have the potential to provide a negative feedback loop to climate change. These fjords are being colonized by organisms on and within the sediment and act as a sink for particulate matter. So far, blue carbon potential in Antarctic habitats has mainly been estimated using epifaunal megazoobenthos (although some studies have also considered macrozoobenthos). We investigated two further pathways of carbon storage and potential sequestration by measuring the concentration of carbon of infaunal macrozoobenthos and total organic carbon (TOC) deposited in the sediment. We took samples along a temporal gradient since time of last glacier ice cover (1–1000 years) at three fjords along the West Antarctic Peninsula. We tested the hypothesis that seabed carbon standing stock would be mainly driven by time since last glacier covered. However, results showed this to be much more complex. Infauna were highly variable over this temporal gradient and showed similar total mass of carbon standing stock per m 2 as literature estimates of Antarctic epifauna. TOC mass in the sediment, however, was an order of magnitude greater than stocks of infaunal and epifaunal carbon and increased with time since last ice cover. Thus, blue carbon stocks and recent gains around Antarctica are likely much higher than previously estimated as is their negative feedback on climate change. Abstract : With increasing climate change, carbon drawdown is becoming more and more important. Polar regions are lacking multicellular plants which are fulfilling this function in other parts of the world. Here, we have shown that, in Antarctica, carbon storage and potential sequestration can occur via three different ways: (1) Sedimentation of particles in the water column to the seafloor; (2) animals living on the seafloor; (3) animals living in the sediment of the seafloor. See commentary on: https://onlinelibrary.wiley.com/doi/10.1111/gcb.15949 ; See Letter to the Editor on https://onlinelibrary.wiley.com/doi/10.1111/gcb.16047 ; See also Response to the Editor on https://onlinelibrary.wiley.com/doi/10.1111/gcb.16048